Correlation Between Co-Design and Psychological Need Satisfaction Based on fNIRs Hyperscanning - Yan Li; Junxian Chen; Wu Song (Applied Sciences)
With the increasing attention paid to user-oriented design and services, the term co-design, a form of user-participatory design, is increasingly mentioned. Previous studies have shown that co-design could better satisfy user needs in process and results, but there are few studies that have been empirically validated through neuroscience methods. Therefore, this study used fNIRS (functional near-infrared spectroscopy) to measure the brain blood oxygen data (HbO2 & Hb) of both “designer” and “user” participants from design and non-design majors during traditional and co-design tasks. The IBS (inter-brain synchronization) between participants was calculated using a wavelet coherence package in Matlab. Research has found significant consistency of DLPFC (dorsolateral prefrontal cortex) and BROCA (pars triangularis Broca’s area) was observed in both tasks, with more significance observed in co-design tasks, and IBS activation was significantly positively correlated with need satisfaction rate. The results showed that co-design could better activate DLPFC and BROCA brain regions compared to traditional design, which further supports previous research and expands the possibility of collaborative task paradigms. The increase in co-design IBS compared to traditional design also represents better collaborative performance, and could provide empirical evidence for participatory design based on neuroimaging.